2014
DOI: 10.1038/npp.2014.185
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Morphology is Associated with Tobacco Cigarette Craving

Abstract: The striatum has a clear role in addictive disorders and is involved in drug-related craving. Recently, enhanced striatal volume was associated with greater lifetime nicotine exposure, suggesting a bridge between striatal function and structural phenotypes. To assess this link between striatal structure and function, we evaluated the relationship between striatal morphology and this brain region's wellestablished role in craving. In tobacco smokers, we assessed striatal volume, surface area, and shape using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
3
37
1
Order By: Relevance
“…Finally, there are several proposed approaches, e.g. (Chakravarty et al, 2013; Gass et al, 2013; Heckemann et al, 2006; Jia et al, 2012; Liao et al, 2013; Shen et al, 2010; Wang and Yushkevich, 2013a; Wolz et al, 2010a; Kotrotsou et al, 2014; Janes et al, 2014), that exploit the novel, unlabeled images to enrich the training data, for instance, by employing automatic segmentations as atlases, or by using them to generate different registration paths between the atlases and the target scan to segment. The former can be seen as a form of self-training (a semi-supervised learning technique in which unlabeled data are automatically classified and added to the pool of training samples).…”
Section: Survey Of Methodological Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there are several proposed approaches, e.g. (Chakravarty et al, 2013; Gass et al, 2013; Heckemann et al, 2006; Jia et al, 2012; Liao et al, 2013; Shen et al, 2010; Wang and Yushkevich, 2013a; Wolz et al, 2010a; Kotrotsou et al, 2014; Janes et al, 2014), that exploit the novel, unlabeled images to enrich the training data, for instance, by employing automatic segmentations as atlases, or by using them to generate different registration paths between the atlases and the target scan to segment. The former can be seen as a form of self-training (a semi-supervised learning technique in which unlabeled data are automatically classified and added to the pool of training samples).…”
Section: Survey Of Methodological Developmentsmentioning
confidence: 99%
“…Many methods have been developed to parcellate the whole brain, segmenting it into a large number of regions (Aljabar et al, 2008; Babalola et al, 2009; Fonov et al, 2012; Han et al, 2009; Heckemann et al, 2010, 2011; Keihaninejad et al, 2010; Kotrotsou et al, 2014; Svarer et al, 2005; Wang et al, 2012; Ledig et al, 2014), while other studies have focused on small sets or individual ROIs, such as the caudate nucleus (van Rikxoort et al, 2007b); the cerebellum (Park et al, 2014; Van Der Lijn et al, 2012; Weier et al, 2014); the amygdala (Hanson et al, 2012; Klein-Koerkamp et al, 2014); the corpus callosum (Ardekani et al, 2014; Gao et al, 2014; Meyer, 2014); the striatum (Janes et al, 2014); the subthalamic nucleus, red nucleus and substantia nigra (Xiao et al, 2014b,a); the ventricles (Chou et al, 2008; Raamana et al, 2014); and, most notably, the hippocampus, which has attracted much attention due to its association with dementia and Alzheimer’s disease (Akhondi-Asl et al, 2010; Bishop et al, 2010; Clerx et al, 2013; Hammers et al, 2007; Iglesias et al, 2010; Kim et al, 2012; Leung et al, 2010; Pipitone et al, 2014; Pluta et al, 2012; Raamana et al, 2014; van der Lijn et al, 2008; Van Der Lijn et al, 2012; Winston et al, 2013; Wolz et al, 2010b; Yushkevich et al, 2010; Platero et al, 2014; Ta et al, 2014). …”
Section: Survey Of Applicationsmentioning
confidence: 99%
“…Experimental evidence has shown that the dorsal striatum mediates tobacco-seeking behaviour following abstinence and tobacco craving provoked by smoking cues (McClernon et al, 2009;Sweitzer et al, 2013;Wang et al, 2007). Recently, Janes et al (2014) demonstrated that caudate volume was significantly, positively associated with state-base craving measured by a questionnaire of smoking urges. In addition, the hedonic response to cigarette smoking was proportional to DA release in the caudate (Barrett et al, 2004).…”
Section: Structural Differences Within Fronto-striatal Circuits Betwementioning
confidence: 98%
“…When participants are presented with words or pictures related to their addiction, they often report an enhancement of their subjective amount of craving, as compared to when they are presented with neutral stimuli (e.g., Janes, Park, Farmer, & Chakravarty, 2014;Lovett, Ham, & Veilleux, 2015;Michalowski & Erblich, 2014). This implies that exposure to addiction-related cues enhances craving.…”
mentioning
confidence: 96%